Socio-educational intervention through virtual learning platforms the e-APSA case: El caso E-APSA (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
Virtual learning environments (EVA) allow the creation of processes where training and didactic interaction between teachers and students occur through courses, virtual tutorials, forums, etc., regardless of their location and the time at which they access.The objective of this work is to evaluate the EVA e-APSA, created with the aim of supporting communication and socio-educational intervention in the APSA association, an NGO aimed at people with intellectual disabilities and their environment to improve their quality of life, maximizing their autonomy and the development of their potential.